Design and Implementation of Portable Nebulizer - Fatima falh Mahdi; Heba Allah Raydh Hassan (American Journal of Botany and Bioengineering, 2025)
The chemical diagnosis of renal and hepatic function is a fundamental aspect of modern clinical practice, yet challenges persist in the accuracy and reliability of traditional biomarkers. This study addresses gaps in current diagnostic methodologies by evaluating emerging biochemical markers and advanced detection techniques. A comprehensive review of literature and clinical data was conducted to assess the effectiveness of standard tests such as blood urea nitrogen (BUN), creatinine, alanine transaminase (ALT), and aspartate transaminase (AST), alongside novel biomarker developments. Findings suggest that integrating innovative diagnostic tools, including proteomics and metabolomics, can enhance early disease detection and treatment monitoring. The results emphasize the need for precision medicine approaches, leading to improved patient outcomes and more personalized healthcare strategies.